Determinants of first-line antiretroviral treatment failure among adult HIV patients at Nekemte Specialized Hospital, Western Ethiopia: Unmatched case-control study. (June 2021) - Desalegn, Mengistu; Seyoum, Dejene; Tola, Edosa Kifle; Tsegaye Gayesa, Reta
Objective: In Ethiopia, only a few studies were conducted to determine factors contributing to antiretroviral treatment failure, in general, and there are no published data in the study area, in particular. Thus, the aim of the study was to assess the determinants of first-line treatment failure among adult HIV patients on antiretroviral treatment at Nekemte Specialized Hospital, western Ethiopia. Methods: The hospital-based 1:2 unmatched case–control study was conducted in Nekemte Specialized Hospital from 1 August to 30 September, 2019, on 252 HIV-positive patients receiving antiretroviral treatment (86 cases and 166 controls). Cases were selected from patients who were switched to second-line antiretroviral treatment regimen after first-line antiretroviral treatment failure. Controls were from those who are on the first-line antiretroviral regimens for at least 6 months. Data were collected by two trained clinical nurses. Record review and an interviewer-administered questionnaire were used to collect data. Data were entered into Epi-Data, version 7.2.2, and then exported to SPSS, version 25, for analysis. The association between treatment failure and each covariate was assessed by bivariate analysis to identify candidate variables at p value < 0.25. All candidate variables were entered into multivariate analysis done in stepwise backward likelihood ratio to declare statistical significance association at p value < 0.05, 95% confidence interval. Results: Data from a total of 252 (86 cases and 166 controls) patients were extracted at a response rate of 98.4%. Statistically higher odds of first-line treatment failure were observed among those who started treatment at an advanced stage (Baseline World Health Organization stage 3 o r4 (adjusted odds ratio = 3.12, 95% confidence interval: 1.55–6.26), lower Baseline CD4 count < 100 cells (adjusted odds ratio = 3.06, 95 % confidence interval: 1.45–6.50), lack of participation in a support group (adjusted odds ratio = 4.03, 95% confidence interval: 1.98–8.21), history of antiretroviral treatment discontinuation for greater than 1 month (adjusted odds ratio = 2.36, 95% confidence interval: 1.17–4.78) and poor adherence to antiretroviral treatment (adjusted odds ratio = 3.09, 95% confidence interval: 1.54–6.19). Conclusion: Antiretroviral treatment initiation at an advanced stage, lower CD4 count, no participation in a support group, and poor adherence were determinants of treatment first-line antiretroviral treatment failure. Therefore, health care providers and program developers should give special attention to; early diagnosis and start of treatment, encouraging patients to participate in a support group, trace patients early, and attentively follow patients to improve their adherence to antiretroviral treatment.